EFFECTS OF PRENATAL YOGA ON MATERNAL BLOOD GLUCOSE IN WOMEN WITH GESTATIONAL DIABETES MELLITUS: LITERATUR REVIEW - Isabella, Isabella Amandine Br Siregar; Napitupulu, Purnama Putri Indah; Ariska Fauzianty; Manurung, Herna Rinayanti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Gestational diabetes mellitus (GDM) is a growing public health concern that affects approximately 4–5% of pregnancies in the United Kingdom and may lead to adverse outcomes for both mothers and their infants if not properly managed. Various non-pharmacological interventions have been explored to improve glycemic control during pregnancy, including yoga, which has been shown to provide physical and psychological benefits in low-risk pregnancies. This systematic review aimed to evaluate the effectiveness of yoga in reducing blood glucose levels among pregnant women diagnosed with GDM. A comprehensive literature search was conducted using Ovid databases, PubMed, and CINAHL to identify randomized controlled trials comparing yoga interventions with standard care or control groups, with blood glucose levels measured before and after the intervention. Three studies met the inclusion criteria and were included in the analysis. Overall, the findings demonstrated that participants who engaged in yoga experienced a greater reduction in blood glucose levels compared to those in the control groups. These results suggest that yoga may serve as a safe and beneficial complementary exercise for pregnant women with GDM. However, further studies, particularly in the Indonesia, are required to assess the clinical feasibility, long-term effectiveness, and broader implementation of yoga interventions in pregnancies complicated by gestational diabetes mellitus.